Selected writings - Emerson, Ralph Waldo, 1803-1882.; Baker, Laura; Johnson, Cynthia, 1969- (New York : Simon and Schuster Paperbacks, 2009)
This Enriched Classic edition includes: A concise introduction that gives the reader important background information ; A chronology of the author's life and work ; A timeline of significant events that provides the book's historical context ; An outline of key themes to guide the reader's own interpretations ; Detailed explanatory notes ; Critical analysis and modern perspectives on the work ; Discussion questions to promote lively classroom and book group interaction ; A list of recommended related books and films to broaden the reader's experience.
Introduction -- Chronology of Ralph Waldo Emerson's life and work -- Historical context of the writings of Ralph Waldo Emerson. ADDRESSES AND ESSAYS : The American scholar -- The divinity school address, Nature, Self-reliance -- The Over-soul -- Circles -- The poet -- Experience -- Politics -- Montaigne ; or, The skeptic -- Thoreau -- The transcendentalist -- Fate. POEMS: Uriel -- The rhodora -- The snow-storm -- Threnody -- Concord hymn -- Brahma -- The Sphinx -- Each and all -- The problem -- Hamatreya -- The humble-bee -- Ode -- Give all to love -- Days -- Terminus. Notes -- Interpretive notes -- Critical excerpts -- Questions for discussion -- Suggestions for the interested.
Faculty
Keywords: English poetry